Extrapleural pneumonectomies for pleural mesothelioma. (2nd January 2020) - Faccioli, Eleonora; Bellini, Alice; Mammana, Marco; Monaci, Nicola; Schiavon, Marco; Rea, Federico
ABSTRACT: Introduction : Malignant pleural mesothelioma (MPM) is a fatal malignancy for which there is no definitive cure. The most effective multimodality treatment in prolonging survival is still matter of debate. Surgery remains one of the cornerstones in the multimodality therapy for MPM. Extra-pleural pneumonectomy and pleurectomy/decortication are the two main curative-intent procedures; however, the superiority of one technique over the other is still debated. This review aims to assess short- and long-term results of extrapleural pneumonectomy for MPM. Areas covered : This article focuses on the role of extrapleural pneumonectomy in MPM. A systematic review was performed by using electronic databases to identify studies that included patients treated by this procedure for MPM. Endpoints included overall survival, disease-free survival, recurrence rate, perioperative mortality, and morbidity. Expert commentary : This paper offers an overview of the results that are currently obtained in patients undergoing extrapleural pneumonectomy for MPM. The benefit of surgical treatments in MPM is still debated and its primary goal should be the achievement of a macroscopic complete resection. Several alternative multimodality protocols exist, with specific advantages and drawbacks; therefore, individualization of care for each patient is fundamental. The complexity of the surgical treatment mandates that patients be referred to specialized centers.